1971
DOI: 10.1039/j29710001585
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sensitivities to substituent effects of five-membered heteroaromatic rings in gas phase ionization

Abstract: The molecular ionization potentials of a number of substituted furans, thiophens, selenophens, and pyrroles have been determined by the electron-impact technique. The p value for this reaction is more negative than that for the most selective electrophilic substitutions. The sensitivity to substituent effects appears to vary in the reverse order to that of the ' ground-state aromaticity ' of the rings (furan > pyrrole > thiophen > benzene).THE relative magnitudes of substituent effects in fivemembered heteroar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 0 publications
6
12
3
Order By: Relevance
“…The experimental value obtained by Linda et al [59], (885.7 ± 4.8) kJ Á mol À1 , differs by 16.8 kJ Á mol À1 from the result computed in this work {(868.9 kJ Á mol À1 )}. Similar enthalpic differences between the experimental and calculated data obtained with the same G3(MP2)//B3LYP approach were found for 2-and 3-fluoroanilines [60], as well as for 2-acetylpyrrole [9].…”
Section: Other Gas-phase Thermodynamic Propertiescontrasting
confidence: 80%
“…The experimental value obtained by Linda et al [59], (885.7 ± 4.8) kJ Á mol À1 , differs by 16.8 kJ Á mol À1 from the result computed in this work {(868.9 kJ Á mol À1 )}. Similar enthalpic differences between the experimental and calculated data obtained with the same G3(MP2)//B3LYP approach were found for 2-and 3-fluoroanilines [60], as well as for 2-acetylpyrrole [9].…”
Section: Other Gas-phase Thermodynamic Propertiescontrasting
confidence: 80%
“…The sequence of the highest occupied molecular orbitals of the molecule has been studied by UV photoelectron spectroscopy [17][18][19][20][21][22] and semiempirical calculations. 19,21,23 The ordering of the outer valence molecular orbitals is the same as that of the unsubstituted molecule: 24 2 (b 1 ) 2 3 (a 2 ) 2 , in the C 2v notation, giving an X 1 A 1 electronic ground state.…”
Section: The 2-methyl Furan Moleculementioning
confidence: 99%
“…The overall shape of the photoionization cross section of 2EF is very similar to that of 2MF. The literature ionization energies of 2EF and 2MF are 8.45 ± 0.05 and 8.38 ± 0.03 eV, respectively, which are very comparable with each other. These values are also very similar to our experimentally observed ionization energies for 2EF and 2MF of 8.43 ± 0.05 and 8.40 ± 0.05 eV, respectively.…”
Section: Resultsmentioning
confidence: 76%
“…Figure shows the photoionization spectrum of 2EF obtained from this experiment, with the corresponding photoionization cross section values listed in Table . From these data, it was identified that the threshold for 2EF ionization at 8.43 ± 0.05 eV agrees very well with the literature value of 8.45 ± 0.05 eV, and the CBS‐QB3 calculated AIE of 8.40 ± 0.05 eV. 2EF exhibits a shoulder at 10.0 ± 0.1 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation